Depression among Asian Americans: Review and Recommendations. (27th September 2011) - Kalibatseva, Zornitsa; Leong, Frederick T. L.
Abstract : This article presents a review of the prevalence and manifestation of depression among Asian Americans and discusses some of the existing issues in the assessment and diagnosis of depression among Asian Americans. The authors point out the diversity and increasing numbers of Asian Americans and the need to provide better mental health services for this population. While the prevalence of depression among Asian Americans is lower than that among other ethnic/racial groups, Asian Americans receive treatment for depression less often and its quality is less adequate. In addition, the previous belief that Asians somatize depression may become obsolete as more evidence appears to support that Westerners may "psychologize" depression. The cultural validity of the current DSM-IV conceptualization of depression is questioned. In the course of the review, the theme of complexity emerges: the heterogeneity of ethnic Asian American groups, the multidimensionality of depression, and the intersectionality of multiple factors among depressed Asian Americans.